Profiling the impact of thermal processing on black raspberry phytochemicals using untargeted metabolomics. (15th February 2019) - Teegarden, Matthew D.; Schwartz, Steven J.; Cooperstone, Jessica L.
Highlights: Metabolomics is useful for broadly describing the chemistry of berry foods. Metabolomics uncovered flavonoid/phenolic thermal degradants in black raspberries. Modulation of ellagitannin profile was observed. Key phytochemicals were surveyed and demonstrated stability over thermal processing. Abstract: Clinical and laboratory studies have implicated black raspberries (BRBs) and their associated phytochemicals in the modulation of several chronic diseases. Most research on the health benefits of BRBs is conducted using freeze-dried or otherwise minimally processed products, yet BRBs are typically consumed as thermally processed goods like jams and syrups. The objective of this work was to profile the chemical changes that result from thermal processing of BRB powder into a nectar beverage. Using an untargeted UHPLC-QTOF-MS metabolomics approach, key degradation products of anthocyanins were identified along with several other proposed phenolic degradants. The effects of processing on other key BRB compound groups, including ellagitannins, are also discussed. This work demonstrates the utility of an untargeted metabolomics approach in describing the chemistry of complex food systems and provides a foundation for future research on the impact of processing on BRB product bioactivity.